Durable Continuous-Flow Mechanical Circulatory Support: State of the Art - Antonio Loforte; Luca Botta; Silvia Boschi; Gregorio Gliozzi; Giulio Giovanni Cavalli; Carlo Mariani; Sofia Martin Suarez; Davide Pacini (Hearts, 2021)
Implantable mechanical circulatory support (MCS) systems for ventricular assist device (VAD) therapy have emerged as an important strategy due to a shortage of donor organs for heart transplantation. A growing number of patients are receiving permanent assist devices, while fewer are undergoing heart transplantation (Htx). Continuous-flow (CF) pumps, as devices that can be permanently implanted, show promise for the treatment of both young and old patients with heart failure (HF). Further improvement of these devices will decrease adverse events, enable pulse modulation of continuous blood flow, and improve automatic remote monitoring. Ease of use for patients could also be improved. We herein report on the current state of the art regarding implantable CF pumps for use as MCS systems in the treatment of advanced refractory HF.